The reality of 13 years of prenatal care to pregnant women with syphilis in Sergipe state (2007–2019) - Farias, Rute de Oliveira; Lopes, Izailza Matos Dantas; Santos, Letícia Goes; Dantas, Amanda Silveira de Carvalho (Brazilian Journal of Sexually Transmitted Diseases, 2019)
Introduction: Syphilis is an infectious disease caused by Treponema pallidum, its two main routes of transmission are sexual and transplacental (vertical). The latter is of particular worrisome, since it can generate congenital syphilis and can be avoided by early maternal serological screening. Objective: To analyze the conditions of prenatal care for syphilitic pregnant women in Sergipe State between 2007 and 2019. Methods: A cross-sectional, retrospective, and descriptive study was carried out, with the collection of notified cases of gestational and congenital syphilis in the Brazilian Notifiable Diseases Information System (Sistema de Informação de Agravos de Notificação - SINAN). Results: There was a considerable increase in the number of reported cases of gestational syphilis in the last 13 years. About 36% of pregnant women were identified in the 3rd trimester of pregnancy, 68.1% were brown, 56.8% had studied for up to 8 years, and 50.1% were between 20 and 29 years old. The clinical phase latent to the diagnosis was responsible for 70.3% of the cases, followed by the primary (11%) and tertiary (7.3%) phases. Of the total number of pregnant women, 20.2% did not perform the non-treponemal test, and 97.2% were treated with penicillin. Regarding the numbers of congenital syphilis, although 75% of the mothers performed prenatal care, 37.8% received the diagnosis at the time of delivery/curettage, resulting in 72.9% of infant deaths from the disease. Moreover, there was a predominance of untreated partners (77.7%) in relation to those treated (10.8%). Conclusion: Although most of them performed prenatal care, there was a predominance of diagnoses performed only in the 3rd trimester of pregnancy, mainly at the time of delivery or curettage, not respecting the minimum therapeutic interval of 30 days before delivery. Thus, in Sergipe State, the most important factor in the high prevalence of vertical transmission of syphilis is the ineffectiveness of prenatal care provided to infected pregnant women, which remains.